PHYSIOLOGICAL ROLE OF CALCIUM AND VITAMIN D: OPPORTUNITIES OF NUTRITIONAL CORRECTION OF DEFICIENCY IN PRE-SCHOOLCHILDREN AND YOUNGER SCHOOLCHILDREN - O.V. Stennikova; L.V. Levchuk ("Paediatrician" Publishers LLC, 2010)
One of actual problems of prophylactic pediatrics is provision of schoolchildren with vitamins and minerals. The article summarizes the data on physiological role of calcium and vitamin D, the causes of origin, prevalence and clinical symptoms of its deficiency in children. The opportunities of its correction with food, fortified with vitamins and microelements are described. The norms of daily use of calcium and vitamin D for pre-schoolchildren and younger schoolchildren are given. Key words: children, calcium, vitamin D, deficiency, nutritional correction. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):141-145)